2011
DOI: 10.1007/s00464-011-1761-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic single-site totally extraperitoneal adult inguinal hernia repair: initial 100 patients

Abstract: Based on our experience, in the hands of experienced laparoscopic surgeons, LESS TEP repair for adult inguinal hernia using the homemade port as an access platform is feasible and safe and provides acceptable operative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…15,19,35,37,38,41,42,44,47 Seven studies used a single port access device. 15,19,36,38,39,41,43 Other techniques included the use of 3 ports through a single incision.…”
Section: Surgical Techniquementioning
confidence: 99%
See 3 more Smart Citations